Population regulation in sexual and asexual rotifers: an eco-evolutionary feedback to population size? - Stelzer, Claus-Peter (Funct Ecol, 2012)
1. Population size is often regulated by density dependence, that is negative feedbacks between growth and population density. Several density-dependent mechanisms may operate simultaneously in a population. 2. In this study, I focus on two different mechanisms of density-dependent population regulation, resource exploitation (RE) and density-dependent sexual reproduction (DDS). 3. I analyse both mechanisms in clonal populations of the rotifer Brachionus calyciflorus, which differ in the investment in sex because of a polymorphism at a single Mendelian locus. Some clones were cyclical parthenogens (CP) and possessed both mechanisms of population regulation (RE + DDS), while other clones were obligate parthenogens (OP) and thus lacking the DDS mechanism. 4. Equilibrium population size was considerably lower in CP clones, compared with OP clones, regardless of the exact measurement variable for population size (numbers of individuals or total biovolume/biomass). Interestingly, the decrease in population size was most pronounced in CP clones that heavily invested in sexual reproduction. 5. This suggests that the DDS mechanism can significantly contribute to population regulation and that genotypes lacking this mechanism (because of a mutation in genes affecting this trait) reach substantially higher population sizes. Apparently, the DDS mechanism operates already at much lower population densities than the RE, causing CP populations to stop growing before they are limited by resources. 6. As these differences in population regulation were caused by genetic variation within a single species and as rapid selective sweeps by OP clones are common in B. calyciflorus, this study provides an example for an eco-evolutionary feedback on an important ecological variable – equilibrium population size.